3(x+4)-5=4x-(2x+3)

Simple and best practice solution for 3(x+4)-5=4x-(2x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+4)-5=4x-(2x+3) equation:


Simplifying
3(x + 4) + -5 = 4x + -1(2x + 3)

Reorder the terms:
3(4 + x) + -5 = 4x + -1(2x + 3)
(4 * 3 + x * 3) + -5 = 4x + -1(2x + 3)
(12 + 3x) + -5 = 4x + -1(2x + 3)

Reorder the terms:
12 + -5 + 3x = 4x + -1(2x + 3)

Combine like terms: 12 + -5 = 7
7 + 3x = 4x + -1(2x + 3)

Reorder the terms:
7 + 3x = 4x + -1(3 + 2x)
7 + 3x = 4x + (3 * -1 + 2x * -1)
7 + 3x = 4x + (-3 + -2x)

Reorder the terms:
7 + 3x = -3 + 4x + -2x

Combine like terms: 4x + -2x = 2x
7 + 3x = -3 + 2x

Solving
7 + 3x = -3 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
7 + 3x + -2x = -3 + 2x + -2x

Combine like terms: 3x + -2x = 1x
7 + 1x = -3 + 2x + -2x

Combine like terms: 2x + -2x = 0
7 + 1x = -3 + 0
7 + 1x = -3

Add '-7' to each side of the equation.
7 + -7 + 1x = -3 + -7

Combine like terms: 7 + -7 = 0
0 + 1x = -3 + -7
1x = -3 + -7

Combine like terms: -3 + -7 = -10
1x = -10

Divide each side by '1'.
x = -10

Simplifying
x = -10

See similar equations:

| V-7=40 | | 2(x+4)-2=4x-(3x+2) | | 13x-9=-2(-4x-3) | | 3/4m=75 | | 20x-7=-3(-4x-3) | | 21+3c-7(2-3c)=4(c-5)3c+27 | | (8x^3)-(14y)+(12x)=0 | | 1/14b=-2.39 | | 0.37=ln(-2.5k) | | -0.994=ln(-2.5k) | | lnx=2.25 | | 6cos^2x-17cosx+7=0 | | 9=1/2a | | -3x^2+14x+49=-42 | | 2e^5x=14 | | -3x^2+14x+49=42 | | 6.1=x+(-7.3) | | 6cos^2x-17x+7=0 | | 7(x+7)=-11-3x | | -6(1-8k)=-20 | | 5-(-7*-4)=-33 | | 3y=7x-1 | | -28=12+2z | | (2-x).5=10 | | ln(1+x)-lnx=.25 | | -5x-10=5x | | 4(6x+7)=-40+7x | | 6x+15=9x+13-5x | | 16+4r=8(2+7r) | | 8y+6=3x | | 16x^2+3x+1=0 | | x+(x+1)=380 |

Equations solver categories